Designing Impedance Networks Converters - Zhang, Guidong (Studies in Systems, Decision and Control, 2018)
Research and application of impedance network converters are very popular in recent years, but it still lacks of understanding of and guidelines of impedance networks application, therefore, there is quiet a large potential market about impedance networks converters. This book can serve as a teaching material for graduates and guidelines for engineers as designing an impedance source converter. The main purpose of this book is to understand impedance networks of nonlinear switch circuits and impedance networks matching, which will further put forward understanding of all power converters in view of impedance networks. Taking the impedance network matchings into account leads to a set of criteria for designing an impedance source converter, which is to replace the traditional tedious, manual and experience-dependent design methods.